Quality of Life and Chemosensory Function in Post-COVID Patients: Adherence to Olfactory Training - Wiederstein, Stephanie; Grasl, Stefan; Rappold, Verena; Stueckler, Johanna; Schneeberger, Roswitha; Mueller, Christian A.; Renner, Bertold (Annals of Otology Rhinology and Laryngology, 2025)
Objective: To evaluate adherence to and effects of standardized olfactory training (OT) after COVID-19 infection. Methods: In this prospective study, 475 patients (mean age 47.4/SD 9.5 years) with olfactory dysfunction (OD) after COVID-19 infection participated in OT on average 13 months (range 0-31 months) post-infection. Patients were assessed 3 times with an average interval of 3 months using questionnaires on quality of life (QoL), chemosensory functions, and OT adherence. Results: Overall, 363 patients (76.4%) took part in the first 2 and 49.1% in all 3 testing sessions. Before the initial assessment, 32.8% had performed OT in the past without any instructions, so that merely 9.1% adhered to recommended standards. By the second evaluation, after standardized OT was introduced to the participants, 31.1% (n = 106) reported following the training as recommended, decreasing to 18.5% (n = 43) by the third assessment, indicating that most participants did not complete the recommended duration of at least 12, preferably 24 to 36 weeks of olfactory training. QoL and subjective olfactory acuity significantly improved between the first and following testing sessions (P < .001), but these improvements were not associated with adherence to OT. However, male sex (P = .035), non-medical profession (P = .025), increased age (P = .009), and reduced QoL (P = .027) were observed factors for advanced training adherence to recommended standards. Conclusion: Overall, only a small proportion of participants consistently followed OT. Higher adherence, however, was associated with male sex, non-medical profession, older age, and greater impairment in QoL. Nevertheless, on average there was a clear improvement in QoL and subjective sense of smell over the testing period.
CRIS-Team Scopus Importer:2025-12-26
Keywords: adherence; coronavirus; olfaction; olfactory dysfunction; olfactory training; quality of life